IMPLEMENTING ACADEMIC SUPERVISION TO IMPROVE TEACHERS’ SKILLS IN IMPLEMENTING STUDY FROM HOME PROGRAM (SFH) DURING THE COVID-19 PANDEMIC - Agung Riyanta (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine whether the implementation of academic supervision improved teachers’ skills in implementing the Study from Home program (SFH) during the Covid-19 pandemic at SMA Negeri 1 Kubu, Kabupaten Rokan Hilir. Based on the description of the background, problem identification, and problem limitation, the focus of this research was the implementation of academic supervision to improve teachers’ skills in carrying out the Study from Home program (SFH) during the Covid-19 pandemic at SMA Negeri 1 Kubu, Kab. Rokan Hilir. This School Action Research was carried out only at SMA Negeri 1 Kubu, Rokan Hilir under the supervision of the researcher. This location was chosen because it supported the task of school supervisors in determining the implementation of the Study from Home program (SFH) during the Covid-19 pandemic. This research was conducted in two cycles with a duration of approximately one month. The population in this study consisted of 37 teachers at SMA Negeri 1 Kubu, Kab. Rokan Hilir who were under the guidance of the researcher as the school principal. Based on the description of data processing and discussion, it was concluded that the teachers’ pedagogic competence in Cycle I was 57% in the good category and increased in Cycle II to 88%, also in the good category. This indicated that the implementation of academic supervision to improve teachers’ skills in implementing the Study from Home program (SFH) during the Covid-19 pandemic at SMA Negeri 1 Kubu, Kabupaten Rokan Hilir was successful.